Post-Soviet Racisms - Zakharov, Nikolay; Law, Ian (Mapping Global Racisms, 2017)
This book is novel not only in its theoretical framework, which places racialisation in post-communist societies and their modernist political projects at the centre of processes of global racism, but also in being the first account to examine both these new national contexts and the interconnections between racisms in these four regions of the Baltic states, the Southern Caucasus, Central Asia and Belarus, Moldova and Ukraine, and elsewhere. Assessments of the significance of the contemporary geopolitical contexts of armed conflict, economic transformation and political transition for racial discourse are central themes, and the book highlights the creative, innovative and persistent power of contemporary forms of racial governance which has central significance for understanding contemporary societies. The book will be of interest to scholars and students in the areas of racism and ethnicity studies.- Resumé vydavatel